Correlation between Thyroid Hormones Levels and Some Sex Hormones in Pregnancy States - W. Jihad, Tamara; Al. Attar, Huda Y. (Universitas Negeri Surabaya, 2024)
Thyroid diseases in pregnant women pose a significant challenge for physicians, affecting 1.2% of pregnancies. Untreated conditions can lead to obstetric complications and fetal development disorders, including placental abruption, preeclampsia, preterm birth, and fetal death. This research aims to compare levels of thyroid hormones with female sexual hormones such as estrogen and progesterone due to the change in their levels and to establish the relationship between BMI and (T3 and T4) every third during pregnancy. The research included measuring thyroid hormones that include the hormones triiodothyronine (T3), thyroxine (T4), and thyroid-stimulating hormone (TSH). These hormones are associated with female sexual hormones, including progesterone and estrogen, during the three trimesters (first, second, and third). The findings showed that TSH (thyroid-stimulating hormone) levels in the second and third trimesters of pregnancy were significantly different from those in the control group, while the results showed that arose significantly for both hormonal T3 and T4 at all three stages of pregnancy as compared to control at a significant level (p?0.05). According to the results, body mass index (BMI) increased significantly during pregnancy, with the third trimester experiencing the greatest increase compared to the control group. The third trimester of pregnancy experienced the biggest increase in female sex hormones compared to the control group, with levels of estrogen and progesterone peaking during these three trimesters (p?0.05). During the three pregnancy periods, progesterone and estrogen demonstrated a significant and opposite connection with thyroid-stimulating hormone (TSH) compared to the control group (p?0.05). The research aims to investigate the impact of pregnancy trimesters on thyroid and sexual hormones and the need for improved diagnosis and treatment, especially in the first three months of each phase.